Preliminari Eksperimen dalam Penginduksian Akar Stek Tumbuhan Tetrastigma papillosum Inang Rhizanthes deceptor - Chairul Chairul; Rizka Sefmaliza; M. Idris (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Tetrastigma is a genus in the Vitaceae family which is characterized by the presence of tendrils. This plant has a liana habit, which requires tall plants as support in its life. Induction of host roots, Tetrastigma papillosum, in this study, used Naphthalene Acetic Acid (NAA), which is a class of auxin that functions to induce cell expansion and initiation of rooting. This research was conducted using a Completely Randomized Design (CRD) with 5 treatments and 5 replications. Several NAA concentrations as treatments consist of A (0 ppm), B (2.5 ppm), C (5 ppm), D (7.5 ppm), and E (10 ppm). Root induction of Tetrastigma papillosum can be initiated with NAA at small concentrations because endogenous auxin induces roots more quickly.